URGENSI PELATIHAN DALAM PENGEMBANGAN SUMBER DAYA MANUSIA DI MUSEUM PUSAKA NIAS - Incar Maximilian Hia; Ayler Beniah Ndraha (FEB Universitas Sam Ratulangi Manado, 2023)
Abstract. This study aims to find out how the training in human resource development is carried out by the Nias Heritage Museum. This institution is the only museum that is a place for preserving Nias culture in the Nias Islands. Apart from that, the Nias Heritage Museum also has several business units such as: Lodging (Guesthouse), Café Museum, Rental hall (meeting room), production of Nias traditional medicine, zoo (mini zoo), so that the people in it play a role in services to guests/visitors. So this research will explain the urgency of training in human resource development at the Nias Heritage Museum. The type of research conducted is qualitative research and is descriptive in nature, namely research that describes the urgency of training in human resource development. Data collected by means of interviews, observation, and documentation. The data analysis technique used is data reduction, data presentation and conclusion. The results of the study show that training in human resource development at the Nias Heritage Museum tends to be carried out in the form of briefings or sharing sessions, but this is not optimal in developing human resources at the Nias Heritage Museum, while the implementation of formal training is carried out in certain situations when management identifies serious weaknesses in certain business units.